Bharat rising of viswaguru - Singh, Vivek (New Delhi Rudra World, 2022)
"Bharat Rising of Vishwa Guru" is a compelling book that delves into the remarkable journey of Narendra Modi, the Prime Minister of India, and his significant contributions to transforming India into a global leader. Authored by Dr. Vivek Singh, an astute observer of Indian politics, this book offers a comprehensive exploration of Modi's vision, strategies, and policies that have played a pivotal role in shaping India's position as a world guru. The book begins by providing a detailed account of Modi's humble beginnings and his rise to power in the contemporary Indian political landscape. It beautifully captures the essence of his charismatic personality, highlighting his tenacity, resilience, and unwavering commitment to the nation. The author skillfully unravels the inspiring narrative behind Modi's struggle-filled childhood and presents a vivid portrayal of the physical and mental attributes that have fuelled his love for the country. Throughout the chapters, the book meticulously examines Modi's policies, major initiatives, and his approach towards economic and social reforms. It sheds light on his foreign policy engagements and key milestones achieved during his tenure. The book presents an in-depth analysis of Modi's astute leadership and visionary outlook, which have continually propelled India forward. One commendable aspect of this book is its unbiased approach. Rather than simply praising or criticizing Modi, Dr. Vivek SIngh objectively presents the subjects, providing a dedicated space to understand the significance of his actions before offering any praise or critique. This makes the book a valuable resource for comprehending the policies of leaders and nation-building. The writing style and narrative of this book are captivating. Dr. Vivek Singh skillfully weaves together factual information, insightful analysis, and engaging anecdotes, making it an enjoyable and enlightening read.
Keywords: Prime Minister; Narendra Modi